Adherence to a healthy lifestyle and the risk of type 2 diabetes in Chinese adults. (3rd June 2017) - Lv, Jun; Yu, Canqing; Guo, Yu; Bian, Zheng; Yang, Ling; Chen, Yiping; Hu, Ximin; Hou, Wei; Chen, Junshi; Chen, Zhengming; Qi, Lu; Li, Liming; et al.
Abstract: Background: Simultaneously adhering to multiple healthy lifestyle factors has been related to up to 90% reduction in type 2 diabetes (T2DM) incidence in White populations; however, little is known about whether such protective effects persist in other non-White populations. Methods: We examined the associations of six lifestyle factors with T2DM in the China Kadoorie Biobank of 461 211 participants aged 30–79 years without diabetes, cardiovascular diseases or cancer at baseline. We defined low-risk lifestyle factors as non-smoking or having stopped for reasons other than illness; alcohol consumption of <30 g/day; upper quarter of the physical activity level; diet rich in vegetables and fruits, low in red meat and with some degree of replacement of rice with wheat; body mass index (BMI) of 18.5–23.9 kg/m 2 ; and waist-to-hip ratio (WHR) <0.90 (men)/<0.85 (women). Results: During a median of 7.2 years of follow-up, we identified 8784 incident T2DM. In multivariable-adjusted analyses, two important risk factors for developing T2DM were higher BMI and WHR. Compared with participants without any low-risk factors, the hazard ratio [95% confidence interval (CI)] for those with at least three low-risk factors was 0.20 (0.19, 0.22). Approximately 72.6% (64.2%, 79.3%) of the incident diabetes were attributable to the combination of BMI, WHR, diet and physical activity. The population attributable risk percentage (PAR%) of diabetes appeared to be similar for men and women, and higher among urban, older and obese participants. Conclusions: Our findings indicate that adherence to a healthy lifestyle may substantially lower the burden of T2DM in the Chinese population.